Pendampingan Pengembangan Kurikulum Paud Di TK Dharma Wanita 1 Pomahan Desa Pomahan Kecamatan Pulung - Dyah Fajrika Oktavia; Nanik Setyowati (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This article discusses the process of assisting the development of the Early Chilhood Education (PAUD) curriculum using the ABCD approach. The main focus of this article is the process of the mentoring stages carried out at the Dharma Wanita 1 Pomahan Kindergarten, Pomahan village Pulung District. As a companion, theresearcher carried out the process of identifying the constraints and needs faced by TK Dharma Wanita 1 Pomahan. The method used is the ABCD method in which this approach is based on assets, strenghts and potential that exists in Kindergarten dharma Wanita 1 Pomahan.the purpose of this assistance is to create quality and developing early chilhood education institutions in accordance with the needs of the education unit. The result of this mentoring process is that the Kindergarten Dharma Wanita 1 Pomahan is able to develop aspects of the development needed by students by utilizing the resources and environment in Pomahan Village